Avaliação dos motivos de referenciamento ao ambulatório de cardiologia pediátrica da Policlínica Municipal de Sorocaba pela atenção primária: criação de proposta de interação educacional em serviço - Guevara, Virna Maria (2014)
Introduction- The prevalence of congenital cardiovascular disease is of 7 to 10 children in every 1000 live births. The reasons that lead to the referral of a child by primary care physicians are very varied, with cardiac heart murmur being the most common. Amongst other reasons one can find precordial pain, arrhythmia, fatigue, dyspnea, cyanosis, abnormal chest x-ray, abnormal electrocardiogram, medical examination for physical exercise. The present challenge for pediatricians, family physicians and pediatric cardiologists is to develop accurate diagnosis strategies in a cost-effective manner, with the aim of improving the treatment and save resources. Objectives- The objective is to strengthen the network of health care in its primary and secondary levels using cases of Pediatric Cardiology as the strategic condition and develop an interdisciplinary work proposal with the support of a matrix, which optimize the referral system. Material and methods- It is about the exploratory study with descriptive documental analysis from 433 referral letters of patients seen at the Pediatric Cardiology Ambulatory of Policlinic of Sorocaba from January to June 2012, along with the study of the patients medical records. The data collected is quantified using descriptive statistics when relevant. Results- One hundred and sixty-six patients (38,3%) were discharged, 93 with feedback letter of referral (56,0%). Ninetysix (22,2%) missing follow up, 9 of which had confirmed cardiovascular disease, 29 with absence of cardiovascular disease and 58 without a definitive diagnosis of cardiovascular disease. One hundred and seventy-one patients (39,5%) attend follow-ups. Conclusion- With the aim of strengthening the network of health care using recent medical advances, such as telemedicine and the concept of matrix support, as means of exchange, improvement and to save resources and knowledge